Peran Ibu Pekerja sebagai Madrasatul Ula dalam Mendampingi Belajar Anak pada Pembelajaran PAI - Noor Wirakusuma, Ardhi (PT Faliha Cendekia Nusantara, 2024)
Working mothers have a role as Madrasatul Ula for their children. The purpose of this Madrasatul Ula is that a mother figure becomes the first educator for her child. From the time they are in the womb until their child is born, mothers will always foster, guide, direct and educate their children wholeheartedly. But in this decade, the mother also helps in meeting the economic needs of the family. Whereas the figure of a mother is very important in educating her child. Especially learning related to Islam. PAI subject matter is important to be a beacon of life in worship and form individual piety and social piety. So it's really unfortunate if mothers can't accompany their children to study PAI. This study aims to explain how the role of working mothers as Madrasatul Ula in accompanying children's learning in PAI learning. By using a qualitative method approach. Data collection techniques using observation, interviews and documentation. After the data is collected, it will be tested for the validity of the data using interactive analysis methods. The results of the study explain how working mothers as Madrasatul Ula manage their time in the midst of busy work to accompany their children's learning in PAI learning and explain the efforts made by working mothers in accompanying their children's learning.